2020
DOI: 10.3390/agronomy10101553
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Humic Substances and Phenolic Compounds in Regulating Plant-Biological Functionality

Abstract: Significant benefit of soil organic matter (SOM) to crop productivity is scientifically well documented. The main constituents and active fractions of SOM are humic substances (HS) and phenolic compounds. Since both these two components strongly impact plant–soil relationship, it is importantly from an ecological point of view to discriminate their biological effects and relating them to their composition. In this study we compared the biological effects of HS, and the soil water soluble phenols (SWSP) on grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
1
9
0
1
Order By: Relevance
“…Such processes may be mimicking the activity of root exudates, containing low molecular weight organic acids, and influence the molecular size and solubility of HS in the soil [ 53 , 54 ]. In addition, the carboxyl groups also contribute to determining HS solubility and biological reactivity [ 55 , 56 ].…”
Section: Structure Of Humic Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such processes may be mimicking the activity of root exudates, containing low molecular weight organic acids, and influence the molecular size and solubility of HS in the soil [ 53 , 54 ]. In addition, the carboxyl groups also contribute to determining HS solubility and biological reactivity [ 55 , 56 ].…”
Section: Structure Of Humic Substancesmentioning
confidence: 99%
“…As an example, in some research the induction of lateral root emergence was positively correlated with the lignin-derived aromatic component, whereas negatively correlated with cellulose derivatives [ 63 ]. Conversely, simple phenolic compounds, such as hydroxy-substituted benzoic and cinnamic acid derivatives were considered the most active components in other studies [ 56 , 64 ].…”
Section: Relationship Between Structure and Biological Activitymentioning
confidence: 99%
“…Earlier works indicated that plant growth and metabolism are enhanced by humic matter either rich in peptides, carbohydrates and organic acids, but poor in phenols [26] or in tartaric acid and fatty acids [27]. However, other studies suggest that it is not only the molecular composition that has a bearing on plant stimulation but also the conformational arrangement of the humic supramolecular assembly is essential in reaching and activating plant roots [8,10,40].…”
Section: Treatmentsmentioning
confidence: 99%
“…Apart from soil microbiome, other organic matters of the soil such as humic substances (HS) have been known to play a vital role in plant growth, yield, and nutrition [ 106 ]. HS belong to naturally occurring organic substances which originate from the decomposition and transformation of plant, animal, and microbial residues [ 107 , 108 ]. The process of decay and transformation of plants and microbial remains in the soil generates a variety of highly acidic, relatively large, and colorful molecules which constitute HS.…”
Section: Plant and Soil Microbiomementioning
confidence: 99%